Insomnia in shift workers of a zinc smelter - Natalia Pasierb; Karolina Filipczyk; Łukasz Kunert; Magdalena Piegza; Robert Pudlo (Nofer Institute of Occupational Medicine, 2019)
Background The aim of this study was to assess the prevalence of insomnia among the employees of a zinc smelter in Miasteczko Śląskie using the Athens Insomnia Scale . Material and Methods The examined group of plant employees and the control group were asked to fill in a questionnaire composed of the AIS and questions relating to the place and nature of their work, accidents over the last year, medications, diseases and conditions, sleep, naps and sleepiness during the day. Results The result leading to a diagnosis of insomnia as indicated by the AIS was found in significantly more instances in the test group than in the control group (29.5% vs. 8.4%). While comparing the test subgroup, which was not employed in shift-work, with the control group did not result in a statistically significant difference, slightly more respondents from the day-work test subgroup obtained the result of ≥ 8 pts. Conclusions The prevalence of insomnia assessed by means of the AIS in the group of employees of a zinc smelter is significantly higher than in the control group. Based on the AIS, the highest percentage of individuals with insomnia occurred in the subgroup employed in shift-work. Med Pr. 2019;70(5):611-6